PENGARUH MEDIA PEMBELAJARAN INTERAKTIF TERHADAP KEMAMPUAN LITERASI SISWA KELAS III - Morningrum, Roro Dewila; Latifah, Nur; Kurniawan, Eka Yulyawan (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
Learning media is a tool to make learning and teaching activities easier, so that students understand lessons more easily, while interactive media is the use of computers to combine text, graphics, audio, moving images (video and animation) into one unit with links and tools. appropriate so that it allows multimedia users to navigate, interact, create and communicate. And literacy skills are the ability to master knowledge in a particular field when someone uses reading and writing skills to deepen their understanding of a subject or topic. This research aims to determine the effect of interactive learning media on students' literacy skills. The research method used is quantitative experiment. The subjects studied were class III students at SDS Tunas Harapan, Tangerang Regency. Data collection instruments use observation, tests and documentation. The research results show that the average results of the pre-test and post-test are different, thereby indicating the influence of interactive media on literacy skills. The pre-test score before being given treatment in the form of interactive media, the score obtained by the control class was 69.5 and the experimental class was 73.7. Meanwhile, the value obtained in the post-test using interactive learning media, the value obtained by the control class was 84.9 and the experimental class was 88.9.